2009
DOI: 10.1002/jor.20894
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rapamycin on bone growth in rabbits

Abstract: mTOR is a nutrient-sensing protein kinase that regulates numerous cellular processes. Our prior studies using the mTOR inhibitor, rapamycin, indicate an important role for mTOR in chondrogenesis. We extended our observations to a physiological, in vivo model of bone growth, direct infusion of rapamycin into the proximal tibial growth plates of rabbits. Rapamycin or DMSO vehicle was infused directly into growth plates by an osmotic minipump for 8 weeks. Tibial growth was followed radiographically. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
(46 reference statements)
3
33
0
Order By: Relevance
“…Although previous genetic and pharmacological studies have revealed the crucial role of mTORC1 in skeletal development (Chen and Long, 2014, Jiang et al., 2017, Phornphutkul et al., 2008, Phornphutkul et al., 2009, Yan et al., 2016), here we provide evidence demonstrating the critical role of the mTORC1/4E-BPs/SOX9 axis in skeletogenesis. Although it is well-established that Sox9 /SOX9 is the subject of many types of regulatory mechanisms, including epigenetic and transcriptional regulation of its gene, post-transcriptional regulation of its RNA, and post-translational modifications of its protein (Akiyama and Lefebvre, 2011, Kozhemyakina et al., 2015, Lefebvre and Dvir-Ginzberg, 2017), no previous literature has reported the translational control of Sox9 RNA thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous genetic and pharmacological studies have revealed the crucial role of mTORC1 in skeletal development (Chen and Long, 2014, Jiang et al., 2017, Phornphutkul et al., 2008, Phornphutkul et al., 2009, Yan et al., 2016), here we provide evidence demonstrating the critical role of the mTORC1/4E-BPs/SOX9 axis in skeletogenesis. Although it is well-established that Sox9 /SOX9 is the subject of many types of regulatory mechanisms, including epigenetic and transcriptional regulation of its gene, post-transcriptional regulation of its RNA, and post-translational modifications of its protein (Akiyama and Lefebvre, 2011, Kozhemyakina et al., 2015, Lefebvre and Dvir-Ginzberg, 2017), no previous literature has reported the translational control of Sox9 RNA thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Direct infusion of rapamycin in growth plates by an osmotic minipump resulted in smaller hypertrophic and proliferative zones, decrease in the size of the growth plate, and inhibition of overall long bone growth in rabbits [58]. In young rats, treatment with rapamycin significantly decreased endochondral bone growth [59].…”
Section: Mtor In Cartilage Growth and Developmentmentioning
confidence: 99%
“…This potent inhibition of mTOR is likely to account for the cytostatic effects of BEZ235 on MSC growth observed at higher concentrations, given the well-established role of mTOR signaling in regulating protein synthesis. (52,53) To date, the role of mTOR in osteogenesis remains controversial because conflicting studies using rapamycin have reported both negative (54)(55)(56)(57)(58)(59) and positive (24)(25)(26) effects on osteogenesis.…”
Section: Nvp-bez235 Promotes Osteogenesis In Human Mscsmentioning
confidence: 99%